The political economy of fiscal reform in Central-Eastern Europe : Hungary, Poland, and the Czech Republic from 1989 to EU accession - Bönker, Frank (Cheltenham, UK ; Northampton, Mass. : Edward Elgar, 2006)
Examines the necessary conditions for the successful initiation and consolidation of unpopular economic reforms. Drawing on the literature in the area of policy reform, this book features a comparative analysis of fiscal reform in Hungary, Poland and the Czech Republic at different stages of the post-communist transformation.
Includes bibliographical references (p. 164-192) and index.
opc 03/01/17
Loans
Keywords: Fiscal policy; Economic policy; Europe, Eastern